Claims and satisfaction of the business sector regarding the electricity service in the southern part of Peru - Fernandez Argandoña, Regis Andre Junior (2021)
The main objective of this article is to determine the relationship that exists between the application of the complaint handling procedure in the electricity service and satisfaction from the perspective of the businessman from Tacna, in 2019. The type of research was non-experimental of level correlational. The survey was the data collection technique while the instrument was the questionnaire. Having a population of 203 entrepreneurs and applying the instrument to 133 as a representative sample. After applying the respective instruments, it was obtained as a result that there is a significant correlation between the variable application of the complaint handling procedure in the electricity service and the satisfaction variable from the perspective of the businessman from Tacna, 2019. Likewise, a correlation coefficient was found statistically significant positive perfect (P = 0.973), which is why it is concluded that there is a relationship between the application of the procedure for attention to claims of the electricity service and the satisfaction of the businessmen of Tacna.